2017
DOI: 10.1589/jpts.29.880
|View full text |Cite
|
Sign up to set email alerts
|

Interrelationship among the health-related and subjective quality of life, daily life activities, instrumental activities of daily living of community-dwelling elderly females in orthopedic outpatients

Abstract: [Purpose] This study aimed to examine the health-related and subjective quality of life of community-dwelling elderly females in orthopedic outpatients, and also examined how such quality of life correlate with their daily life activities and instrumental activities of daily living. [Subjects and Methods] Subjects were 27 community-dwelling elderly females in orthopedic outpatients (mean age: 76.3 ± 7.4 years). Their health-related quality of life and subjective quality of life, life-space assessment, frenchay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…In Fig. 2(a), the findings of the selected studies revealed that as a person ages, his/her psychological issues are intensified and s/he feels more unmet needs [31–33, 36, 44]. Furthermore, aging is a factor that could increase the range of disabilities, reduce cognitive abilities, and increase problems related to the teeth, swallowing and nutrition [30, 34] –[42].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In Fig. 2(a), the findings of the selected studies revealed that as a person ages, his/her psychological issues are intensified and s/he feels more unmet needs [31–33, 36, 44]. Furthermore, aging is a factor that could increase the range of disabilities, reduce cognitive abilities, and increase problems related to the teeth, swallowing and nutrition [30, 34] –[42].…”
Section: Resultsmentioning
confidence: 99%
“…Quail, Wolfson, and Lippman in 2011 [44] believed that“there are differences in the severity of psychological distress based upon the type of activity in which a woman is disabled (Personal Activities of Daily Living (PADL) versus IADL) and whether the need for physical assistance is met or unmet. The unmet need to perform an IADL is associated with increased psychological distress over and above the level of distress related to meeting the IADL need.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the lower locomotive function of ADL was associated with poor HRQOL (Huang et al, 2018). ADL level was higher for community-dwelling older adults with superior HRQOL (Takemasa et al, 2017). Our study shows the empirical evidence that the higher locomotive, manipulative, stabilize, and posture change function of mobility-related ADL should be sustained in order to prevent the decrease in physical health of HRQOL in healthy older adults.…”
Section: Discussionmentioning
confidence: 99%